The Effects of the 2010 Chilean Natural Disasters on the Stock Market - Ruiz, José Luis; Barrero, Marcelo (Estudios de Administración, 2014)
The 2010 Chilean earthquake and tsunami were among the strongest in the world history. The exogeneity of these natural disasters provides the opportunity to test stock price reactions. Using a sample of 42 firms listed in the Santiago Stock Exchange, we develop an event study methodology considering heterogeneity in volatility. Chilean stock market volatilityincreased by 240% (120%) during the 5 (11) trading days after the earthquake. The results are informative about the behavior of the stock prices: returns are positive in sectors the retail, real estate, and banking sectors and negative in food, steel, and forestry. Insurance coverage decreases the impact on economic growth.